Chlorine-containing crosslinked resin molded body and its manufacturing method
Patent Information
- Application Number
- JP2021055918
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-29
- Publication Date
- 2025-02-17
- Estimated Expiration
- 2041-03-29
Smart Images

Figure 0007630328000001 
Figure 0007630328000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a chlorine-containing crosslinked resin molded article and a method for producing the same. [Background technology]
[0002] Molded products of connecting materials and molding materials attached (attached) to the terminals of various industrial cables (including electric wires) are required to have oil resistance and heat resistance because they are in contact with or immersed in oil such as machine oil, and may be used in high-temperature environments exceeding room temperature (25°C). Compositions containing chlorine-containing resins such as polyvinyl chloride are widely used as materials for forming such molded products. For example, Patent Document 1 describes a vinyl chloride resin composition for injection-molded shoes, which contains 90 to 150 parts by weight of a plasticizer per 100 parts by weight of vinyl chloride resin, and the breakdown of the plasticizer is (a) 30 to 55% by weight of an adipic acid polyester-based plasticizer having a specific molecular weight, and (b) 70 to 45% by weight of (b-1) an adipic acid polyester-based plasticizer having a specific molecular weight and / or (b-2) an adipic acid ester-based plasticizer. Patent Document 2 describes a vinyl chloride resin composition containing, per 100 parts by mass of (A) a vinyl chloride resin, 10 to 100 parts by mass of (B) an ethylene-vinyl acetate-carbon monoxide copolymer and / or an ethylene-(meth)acrylic acid ester-carbon monoxide copolymer, 0 to 100 parts by mass of (C) a plasticizer, 1 to 20 parts by mass of (D) a non-lead stabilizer, and 0 to 50 parts by mass of (E) a flame retardant. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2004-143235 A [Patent Document 2] JP 2013-231134 A Summary of the Invention [Problem to be solved by the invention]
[0004] The above molded bodies have a wide variety of shapes, and are generally manufactured by injection molding (molding using a mold), which can mold precise and diverse (complex) shapes. However, compositions containing chlorine-containing resins, which are suitable as materials for molded bodies that require oil resistance and heat resistance, tend to become highly viscous, and are therefore considered unsuitable for injection molding. For example, in injection molding, if the flowability of the material is not controlled, the amount of material injected into the mold will be insufficient (insufficient), making it impossible to mold the desired shape (poor shape characteristics), and causing injection molding defects such as poor appearance of the molded body. In order to improve the flowability of a composition containing a chlorine-containing resin, it is effective to increase the content of plasticizer, but on the other hand, this causes a decrease in oil resistance and even heat resistance. Moreover, the above-mentioned molded body is required to have high properties such as oil resistance and heat resistance due to the expansion of its applications and high performance. For example, a high level of oil resistance is required to pass an oil resistance test (for example, Japanese Industrial Standards (JIS) C 3005 (2014) 4.18 (oil resistance) condition C) under conditions of a temperature of 120°C and an immersion time of 18 hours. On the other hand, in order to express high heat resistance in a molded body, it is effective to crosslink the chlorine-containing resin (to form a molded body from a crosslinked product). However, chlorine-containing resins, especially polyvinyl chloride, are difficult to crosslink in the first place, and crosslinking requires special equipment such as an electron beam crosslinking method or an organic peroxide crosslinking method, or a crosslinking reaction at high temperatures. Moreover, since a composition containing a chlorine-containing resin usually contains a large amount of plasticizer, it is difficult to express sufficient heat resistance even if the chlorine-containing resin is crosslinked. In this situation, conventional compositions containing chlorine-containing resins, such as those described in Patent Documents 1 and 2, cannot achieve the oil resistance and heat resistance required in recent years, and when injection molding is applied, it cannot effectively prevent the occurrence of injection molding defects. Moreover, it is necessary to use special equipment and carry out a crosslinking process at high temperatures.
[0005] The present invention aims to provide a chlorine-containing crosslinked resin molded article that is free from injection molding defects while having high oil resistance and heat resistance. Another object of the present invention is to provide a method for easily producing a chlorine-containing crosslinked resin molded article that exhibits high oil resistance and heat resistance. [Means for solving the problem]
[0006] The present inventors have intensively studied compositions containing chlorine-containing resins, and have found that by combining a specific ratio of ethylene-carbon monoxide copolymer and a plasticizer with a specific ratio of polyvinyl chloride and chlorinated polyethylene as the base resin constituting the molded body, and then applying a silane crosslinking method as a crosslinking method (coexisting each component required for the silane crosslinking method), a chlorine-containing crosslinkable resin composition that can be injection molded while effectively suppressing the occurrence of injection molding defects can be prepared, and further, by injection molding this crosslinkable resin composition and then silane crosslinking it, a chlorine-containing crosslinked resin molded body that has high oil resistance and heat resistance and is free of injection molding defects can be produced in a simple manner. Based on this knowledge, the present inventors have further studied and have come to the present invention.
[0007] That is, the object of the present invention has been achieved by the following means. <1> A chlorine-containing crosslinked resin molded product obtained by injection molding and then silane crosslinking a silane crosslinking resin composition containing, relative to 100 parts by mass of a chlorine-containing resin, 15 to 70 parts by mass of an ethylene-carbon monoxide copolymer, 30 to 100 parts by mass of a plasticizer, 0.01 to 0.5 parts by mass of an organic peroxide, 0.5 to 50 parts by mass of an inorganic filler, 1 to 10 parts by mass of a silane coupling agent having a grafting reaction site capable of undergoing a grafting reaction with the chlorine-containing resin in the presence of radicals generated from the organic peroxide, and a silanol condensation catalyst, the chlorine-containing resin comprises 20 to 50 parts by mass of chlorinated polyethylene and 50 to 80 parts by mass of polyvinyl chloride, The ethylene-carbon monoxide copolymer comprises at least one of an ethylene-vinyl acetate-carbon monoxide copolymer and an ethylene-(meth)acrylic acid ester-carbon monoxide copolymer; Chlorine-containing cross-linked resin molding. <2> The ethylene-carbon monoxide copolymer is an ethylene-(meth)acrylic acid ester-carbon monoxide copolymer; <1> 2. The chlorine-containing crosslinked resin molding according to claim 1 . <3> The content of the ethylene-carbon monoxide copolymer is 20 to 50 parts by mass relative to 100 parts by mass of the chlorine-containing resin. <1> or <2> 2. The chlorine-containing crosslinked resin molding according to claim 1 . <4> The chlorine-containing resin contains 20 to 35 parts by mass of chlorinated polyethylene and 65 to 80 parts by mass of polyvinyl chloride. <1> ~ <3> 2. The chlorine-containing crosslinked resin molding according to claim 1 . <5> The content of the plasticizer is 50 to 80 parts by mass relative to 100 parts by mass of the chlorine-containing resin. <1> ~ <4> 2. The chlorine-containing crosslinked resin molding according to claim 1 .
[0008] <6> A method for producing a chlorine-containing crosslinked resin molded product, comprising the following steps (1), (2) and (3): Step (1): 100 parts by mass of ethylene-carbon monoxide copolymer is added to 100 parts by mass of chlorine-containing resin. 5 to 70 parts by mass, 30 to 100 parts by mass of a plasticizer, and 0.0 parts by mass of an organic peroxide. 1 to 0.5 parts by mass, an inorganic filler of 0.5 to 50 parts by mass, and the organic peroxide. Grafting with the chlorine-containing resin in the presence of radicals generated from an oxide Silane coupling agents 1-10 having reactive grafting reaction sites and a silanol condensation catalyst are melt-mixed to obtain a silanol condensation catalyst from the organic peroxide. The radicals generated from the grafting reaction site and the chlorine-containing resin are By subjecting the grafting reaction to a graftable site of the fat, A step of preparing a chlorine-containing crosslinkable resin composition Step (2): A step of obtaining a molded product by injection molding the chlorine-containing crosslinkable resin composition. Step (3): A step of contacting the molded product with water to obtain a chlorine-containing crosslinked resin molded product. the chlorine-containing resin comprises 20 to 50 parts by mass of chlorinated polyethylene and 50 to 80 parts by mass of polyvinyl chloride, the ethylene-carbon monoxide copolymer comprises at least one of an ethylene-vinyl acetate-carbon monoxide copolymer and an ethylene-(meth)acrylic acid ester-carbon monoxide copolymer; In carrying out the step (1), A method for producing a chlorine-containing crosslinked resin molded product, wherein, in the case where the whole of the chlorine-containing resin is melt-mixed in the following step (a-2), the step (1) comprises the following steps (a-1), (a-2), and (c), and, in the case where a part of the chlorine-containing resin is melt-mixed in the following step (a-2), the step (1) comprises the following steps (a-1), (a-2), (b), and (c). Step (a-1): Mixing the inorganic filler and the silane coupling agent to form a mixture A step of preparing Step (a-2): Reacting the mixture, all or a part of the chlorine-containing resin, and ethylene monoxide The carbon copolymer and the plasticizer are mixed in the presence of the organic peroxide. The mixture is melted and mixed at a temperature equal to or higher than the decomposition temperature of the peroxide, and the graph The grafting reaction site and the grafting reaction site are subjected to a grafting reaction. preparing a silane master batch by Step (b): Melt-mixing the remainder of the chlorine-containing resin and the silanol condensation catalyst, A process for preparing a catalyst master batch Step (c): The silane master batch and the silanol condensation catalyst or the catalyst master batch are mixed. The chlorine-containing crosslinkable resin composition is prepared by melt-mixing the star batch. The process of
[0009] <7> The ethylene-carbon monoxide copolymer is an ethylene-(meth)acrylic acid ester-carbon monoxide copolymer; <6> The manufacturing method described in <8> The ethylene-carbon monoxide copolymer is melt-mixed in an amount of 20 to 50 parts by mass with respect to 100 parts by mass of the chlorine-containing resin. <6> or <7> The manufacturing method described in <9> The chlorine-containing resin contains 20 to 35 parts by mass of chlorinated polyethylene and 65 to 80 parts by mass of polyvinyl chloride. <6> ~ <8> The method for producing a product according to any one of claims 1 to 5. <10> The content of the plasticizer is 50 to 80 parts by mass relative to 100 parts by mass of the chlorine-containing resin. <6> ~ <9> The method for producing a product according to any one of claims 1 to 5. <11> the above <6> ~ <10> 2. A chlorine-containing crosslinked resin molded article obtained by the method according to claim 1.
[0010] In this specification, a numerical range expressed using "to" means a range that includes the numerical values before and after "to" as the lower and upper limits. Effect of the Invention
[0011] The present invention can provide a chlorine-containing crosslinked resin molded article that has high oil resistance and heat resistance while being free from injection molding defects, and a method for producing a chlorine-containing crosslinked resin molded article that exhibits high oil resistance and heat resistance in a simple manner. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] [Chlorine-containing cross-linked resin molding] The chlorine-containing crosslinked resin molded article of the present invention is a crosslinked resin molded article of a chlorine-containing crosslinkable resin composition described later, specifically, a molded article formed by injection molding a silane crosslinking resin composition described later (preferably, a chlorine-containing crosslinkable resin composition prepared by grafting a silane coupling agent premixed with an inorganic filler in the silane crosslinking resin composition and a chlorine-containing resin), and preferably, a molded article manufactured by the method for manufacturing a chlorine-containing crosslinked resin molded article of the present invention described later. As described above, the chlorine-containing crosslinked resin molded article of the present invention is a molded article without injection molding defects by utilizing the excellent injection moldability (the property that effectively suppresses the occurrence of injection molding defects and enables injection molding) of the chlorine-containing crosslinkable resin composition. This molded article is low-cost and has excellent appearance and shape characteristics, and further has high oil resistance and heat resistance. This chlorine-containing crosslinked resin molded article has a crosslinked structure in which a chlorine-containing resin, usually a chlorinated polyethylene, and further an ethylene-carbon monoxide copolymer are silane-crosslinked (a crosslinked structure via a silane coupling agent or a silanol condensate thereof), and as described below, an inorganic filler may be incorporated in the crosslinked structure, and it is preferable that an inorganic filler is incorporated as part of the crosslinked structure.
[0013] The chlorine-containing crosslinked resin molded product of the present invention and the chlorine-containing crosslinked resin molded product manufactured by the manufacturing method of the present invention can be suitably used as products (including semi-finished products, parts, and members) that require high oil resistance and heat resistance, such as connecting materials and molding materials attached to cable terminals, and further as molded products (molded products) that are substitutes for rubber parts manufactured by injection molding (mold molding). More specifically, in addition to the above connecting materials and molding materials, power plugs, connectors, sleeves, boxes, tape base materials, tubes, sheets, packings, gaskets, cushioning materials, vibration-proof materials, etc. are exemplified. In particular, connecting materials and molding materials attached to heat-resistant cables that require high heat resistance (for example, a level that meets JIS C 3005 (2014) 4.17 (heating)) or the above-mentioned high oil resistance, and packings and gaskets used as vehicle members for automobiles, trains, etc. are preferred.
[0014] [Silane crosslinking resin composition] The silane crosslinking resin composition contains, relative to 100 parts by mass of a chlorine-containing resin, 15 to 70 parts by mass of an ethylene-carbon monoxide copolymer, 30 to 100 parts by mass of a plasticizer, 0.01 to 0.5 parts by mass of an organic peroxide, 0.5 to 50 parts by mass of an inorganic filler, 1 to 10 parts by mass of a silane coupling agent, and a silanol condensation catalyst. This silane crosslinking resin composition can form a chlorine-containing crosslinkable resin composition exhibiting excellent injection moldability by subjecting the silane coupling agent premixed with the inorganic filler to a graft reaction with the chlorine-containing resin and further with the ethylene-carbon monoxide copolymer (step (1) described below), and is suitable for use in the production of molded articles with high oil resistance and heat resistance and no injection molding defects, particularly in the production method of the chlorine-containing crosslinked resin molded article of the present invention.
[0015] [Chlorine-containing crosslinkable resin composition] The chlorine-containing crosslinkable resin composition is a silane-crosslinkable chlorine-containing resin composition obtained by melt-mixing 15-70 parts by mass of an ethylene-carbon monoxide copolymer, 30-100 parts by mass of a plasticizer, 0.01-0.5 parts by mass of an organic peroxide, 0.5-50 parts by mass of an inorganic filler, 1-10 parts by mass of a silane coupling agent having a grafting reaction site capable of undergoing a grafting reaction with the chlorine-containing resin in the presence of radicals generated from the organic peroxide, and a silanol condensation catalyst, relative to 100 parts by mass of the chlorine-containing resin, and grafting the grafting reaction site with the grafting reaction site of the chlorine-containing resin by the radicals generated from the organic peroxide (step (1) described below). This chlorine-containing crosslinkable resin composition contains a silane-crosslinkable chlorine-containing resin obtained by grafting a silane coupling agent bonded or dissociated with an inorganic filler to a chlorine-containing resin, and may also contain a silane-crosslinkable copolymer obtained by grafting an ethylene-carbon monoxide copolymer to a silane coupling agent bonded or dissociated with an inorganic filler. The chlorine-containing crosslinkable resin composition exhibits excellent injection moldability, and is suitable for use in the manufacture of molded articles having high oil resistance and heat resistance and no injection molding defects, particularly in the method for the manufacture of chlorine-containing crosslinkable resin molded articles of the present invention. In this specification, unless otherwise specified, the term "silane-crosslinkable chlorine-containing resin" means both the silane-crosslinkable chlorine-containing resin and the silane-crosslinkable copolymer.
[0016] Each component constituting the chlorine-containing crosslinked resin molded article of the present invention will be described below. Each of the components may be used alone or in combination of two or more.
[0017] <Chlorine-containing resin> The chlorine-containing resin is used as the base resin constituting the chlorine-containing crosslinked resin molded article of the present invention. Although the chlorine-containing resin is usually excellent in oil resistance, the use of a specific chlorine-containing resin described later in the present invention can impart excellent injection moldability to the chlorine-containing crosslinkable resin composition while imparting heat resistance and high oil resistance to the chlorine-containing crosslinked resin molded article. In the present invention, polyvinyl chloride and chlorinated polyethylene are used in combination as the chlorine-containing resin. The chlorine-containing resin may contain a chlorine-containing resin other than polyvinyl chloride and chlorinated polyethylene (sometimes called other chlorine-containing resin), such as polyvinylidene chloride or chloroprene rubber.
[0018] (chlorinated polyethylene) The chlorinated polyethylene is not particularly limited as long as it is a polyethylene in which hydrogen atoms bonded to the polyethylene main chain are replaced with chlorine atoms, and examples thereof include those obtained by chlorinating an ethylene (co)polymer. Chlorinated polyethylene usually has a grafting reaction site of a silane coupling agent and a site capable of grafting reaction in the presence of an organic peroxide, such as an unsaturated bond site of a carbon chain or a carbon atom having a hydrogen atom in the main chain or at its end. Therefore, the chlorinated polyethylene forms a silane crosslinkable chlorine-containing resin in which the silane coupling agent is grafted. The chlorinated polyethylene preferably has a chlorine content of 20% by mass or more, more preferably 25% by mass or more, and even more preferably 30% by mass or more. When the chlorine content is high, high oil resistance is exhibited. The upper limit of the chlorine content is the mass ratio when all hydrogen atoms that can be replaced with chlorine atoms in the polyethylene before chlorination are replaced with chlorine atoms, and cannot be determined unambiguously depending on the molecular weight of the polyethylene before chlorination, the number of hydrogen atoms that can be replaced with chlorine atoms, etc. For example, it is about 75% by mass. The chlorine content refers to the mass ratio of chlorine atoms to the total amount of chlorinated polyethylene, and can be determined by the potentiometric titration method described in JIS K 7229. The mass average molecular weight of the chlorinated polyethylene is not particularly limited and can be appropriately set depending on the properties, applications, and the like.
[0019] (Polyvinyl chloride) The polyvinyl chloride is not particularly limited as long as it is a polymer (homopolymer or copolymer) of polyvinyl chloride. Polyvinyl chloride is usually difficult to undergo grafting reaction with a silane coupling agent. Examples of copolymers of vinyl chloride include copolymers of vinyl chloride and other vinyl monomers (compounds having ethylenic unsaturated bonds). Examples of other vinyl monomers are not particularly limited, and include, for example, ethylene, propylene, vinyl acetate, vinylidene chloride, (meth)acrylic acid, (meth)acrylic acid ester maleic acid, acrylonitrile, fumaric acid, acrylonitrile, alkyl vinyl ether, etc. The average degree of polymerization of polyvinyl chloride is preferably 400 to 3000, more preferably 700 to 2600, and further preferably 700 to 1500. When the average degree of polymerization is within the above range, the occurrence of injection molding defects can be suppressed while providing high heat resistance and oil resistance.
[0020] (Content of each resin) The content of each resin (component) of the chlorine-containing resin is appropriately set within the following ranges so that the total content of chlorinated polyethylene, polyvinyl chloride and other chlorine-containing resins is 100 mass %. The content of chlorinated polyethylene in the chlorine-containing resin is 20 to 50% by mass. In the present invention, since chlorinated polyethylene is used in combination with polyvinyl chloride and ethylene-carbon monoxide copolymer, even if the content of chlorinated polyethylene is 20% by mass or more, the decrease in injection moldability can be effectively suppressed. On the other hand, even if the content is 50% by mass or less, high oil resistance can be realized. The content of chlorinated polyethylene in the chlorine-containing resin is preferably 20 to 35% by mass, more preferably 25 to 35% by mass, in terms of providing high oil resistance and heat resistance and suppressing the decrease in injection moldability. On the other hand, the content of polyvinyl chloride in the chlorine-containing resin is 50 to 80% by mass. In the present invention, since polyvinyl chloride is used in combination with chlorinated polyethylene and ethylene-carbon monoxide copolymer, even if the content of polyvinyl chloride is set to 50% by mass or more, high oil resistance and heat resistance can be realized. On the other hand, excellent injection moldability can be maintained even if the content is 80% by mass or less. The content of polyvinyl chloride in the chlorine-containing resin is preferably 65 to 80 mass%, more preferably 65 to 75 mass%, in order to realize high oil resistance and heat resistance while maintaining excellent injection moldability. The content of the other chlorine-containing resins in the chlorine-containing resin is appropriately determined within a range that does not impair the effects of the present invention, and can be, for example, 15 mass% or less.
[0021] <Ethylene-carbon monoxide copolymer> In the present invention, an ethylene-carbon monoxide copolymer is used in combination with the chlorine-containing resin. This improves the oil resistance to a high level. The ethylene-carbon monoxide copolymer has a site capable of grafting reaction in the main chain or at the end thereof, and can form a silane-crosslinkable copolymer by grafting reaction with a silane coupling agent. The ethylene-carbon monoxide copolymer may be a copolymer of ethylene and carbon monoxide, and is preferably a terpolymer with an acid copolymerization component. The acid copolymerization component is not particularly limited, but may include vinyl esters of carboxylic acids, carboxylic acid compounds such as (meth)acrylic acid, and (meth)acrylic acid ester compounds. The terpolymer may include, for example, an ethylene-vinyl acetate-carbon monoxide copolymer, an ethylene-(meth)acrylic acid ester-carbon monoxide copolymer, and the like, and in terms of injection moldability, an ethylene-(meth)acrylic acid ester-carbon monoxide copolymer is preferred.
[0022] (Ethylene-vinyl acetate-carbon monoxide copolymer) The ethylene-vinyl acetate-carbon monoxide copolymer may be a copolymer of ethylene, vinyl acetate, and carbon monoxide, and various known copolymers can be used without any particular limitation. In the ethylene-vinyl acetate-carbon monoxide copolymer, the content of each component is not particularly limited and can be appropriately set. For example, the ethylene content is preferably 40 to 80 mass%, the vinyl acetate content is 5 to 50 mass%, and the carbon monoxide content is 3 to 30 mass%, and it is also possible to further copolymerize other monomers as necessary. Examples of the ethylene-vinyl acetate-carbon monoxide copolymer include Elbaloy (trade name, manufactured by DuPont).
[0023] (Ethylene-(meth)acrylic acid ester-carbon monoxide copolymer) The ethylene-(meth)acrylic acid ester-carbon monoxide copolymer may be a copolymer of ethylene, (meth)acrylic acid ester, and carbon monoxide, and various known copolymers can be used without any particular limitation. The (meth)acrylic acid ester may be an alkyl ester or an aryl ester, but an alkyl ester is preferred. The alkyl group forming the alkyl ester is preferably a straight chain or a branched chain, and the number of carbon atoms is preferably 1 to 18, more preferably 1 to 6. Examples of the alkyl group include a methyl group, an ethyl group, a propyl group (n-propyl group, isopropyl group), a butyl group (n-butyl group, sec-butyl group, t-butyl group, isobutyl group), a hexyl group, an octyl group, a decyl group, and a dodecyl group. Specific examples of the ethylene-(meth)acrylic acid ester-carbon monoxide copolymer include an ethylene-butyl(meth)acrylate-carbon monoxide copolymer, an ethylene-ethyl acrylate-carbon monoxide copolymer, and an ethylene-methyl acrylate-carbon monoxide copolymer, and an example of a commercially available product is Elbaloy (trade name, manufactured by DuPont). In the ethylene-(meth)acrylic acid ester-carbon monoxide copolymer, the content of each component is not particularly limited and can be appropriately set. For example, the content of ethylene is preferably 40 to 80 mass%, the content of (meth)acrylic acid ester is preferably 15 to 60 mass%, and the content of carbon monoxide is preferably 5 to 30 mass%, and other monomers can be further copolymerized as necessary.
[0024] <Plasticizer> The plasticizer is not particularly limited, and various plasticizers that are usually used for chlorine-containing resins can be used without any particular limitation. For example, low molecular weight plasticizers such as phthalate ester plasticizers, trimellitate ester plasticizers (preferably, trialkyl trimellitate (alkyl group has 8 to 10 carbon atoms)), polyester plasticizers, adipate ester plasticizers, and pyromellitate ester plasticizers, and polymer plasticizers such as polyester plasticizers, vinyl acetate copolymers, and (meth)acrylic acid ester copolymers can be mentioned. Among them, low molecular weight plasticizers are preferred, and from the viewpoint of plasticizing effect, phthalate ester plasticizers, trimellitate ester plasticizers, polyester plasticizers, adipate ester plasticizers, pyromellitate ester plasticizers, and the like are more preferred.
[0025] <Organic peroxide> The organic peroxide generates radicals at least by thermal decomposition, and acts as a catalyst to initiate a grafting reaction of the silane coupling agent to a chlorine-containing resin or the like by a radical reaction (a covalent bond forming reaction between a grafting reaction site of the silane coupling agent and a site capable of grafting reaction of the chlorine-containing resin or the like, also called a (radical) addition reaction). In particular, when the silane coupling agent contains an ethylenically unsaturated group as a grafting reaction site, the organic peroxide acts to initiate a grafting reaction by a radical reaction between the ethylenically unsaturated group and the chlorine-containing resin or the like (including a reaction of abstracting hydrogen radicals from the chlorine-containing resin or the like). The organic peroxide is not particularly limited as long as it generates radicals. For example, an organic peroxide represented by the general formula: 1 -O-O-R 2 , R 3 -OO-C(=O)R 4 , R 5 C(=O)-OO(C=O)R 6 Preferred are compounds represented by the formula: 1 ~R 6 Each independently represents an alkyl group, an aryl group, or an acyl group. R 1 ~R 6 Among these, it is preferable that all of them are alkyl groups, or that one of them is an alkyl group and the remaining is an acyl group.
[0026] Examples of such organic peroxides include those described in paragraph
[0037] of WO 2015 / 046478, the contents of which are incorporated herein by reference as part of the present specification. In terms of odor, coloring, and scorch stability, dicumyl peroxide, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane, and 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexyne-3 are preferred.
[0027] The decomposition temperature of the organic peroxide is preferably 120 to 195° C., particularly preferably 125 to 180° C. The decomposition temperature of the organic peroxide is equal to or lower than the melt mixing temperature in the step (a-2) described below. In the present invention, the decomposition temperature of an organic peroxide means the temperature at which a single-component organic peroxide undergoes a decomposition reaction into two or more compounds when heated at a certain temperature or temperature range. Specifically, it means the temperature at which heat absorption or heat generation begins when heated from room temperature at a temperature increase rate of 5°C / min in a nitrogen gas atmosphere by thermal analysis such as DSC method.
[0028] <Inorganic filler> In the present invention, the inorganic filler can be used without any particular limitation as long as it has a site on its surface that can form a hydrogen bond or the like with a reactive site such as a silanol group of a silane coupling agent, or a site that can be chemically bonded by a covalent bond. Examples of the site in the inorganic filler that can be chemically bonded with a reactive site of a silane coupling agent include OH groups (hydroxyl groups, water molecules of water of water or crystallization, OH groups such as carboxyl groups), amino groups, and SH groups.
[0029] Examples of inorganic fillers that can be used include metal hydrates such as aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, calcium silicate, magnesium silicate, calcium oxide, magnesium oxide, aluminum oxide, aluminum nitride, aluminum borate whiskers, hydrated aluminum silicate, hydrated magnesium silicate, basic magnesium carbonate, and compounds having hydroxyl groups or water of crystallization, such as hydrotalcite, boron nitride, silica (crystalline silica, amorphous silica, etc.), carbon black, clay, zinc oxide, tin oxide, titanium oxide, molybdenum oxide, antimony trioxide, silicone compounds, quartz, talc, zinc borate, white carbon, zinc borate, zinc hydroxystannate, and zinc stannate. Of these, the inorganic filler is preferably a metal hydrate (more preferably magnesium hydroxide), calcium carbonate, hydrotalcite, talc, clay, silica, or carbon black, or a mixture thereof.
[0030] The average particle size of the inorganic filler is preferably 0.2 to 10 μm, more preferably 0.3 to 8 μm, further preferably 0.4 to 5 μm, and particularly preferably 0.4 to 3 μm. The average particle size is determined by dispersing the inorganic filler in alcohol or water and using an optical particle size measuring device such as a laser diffraction / scattering particle size distribution measuring device.
[0031] The inorganic filler may be surface-treated with a silane coupling agent or the like. For example, silane coupling agent surface-treated metal hydrates include Kisuma 5L and Kisuma 5P (both trade names, magnesium hydroxide, manufactured by Kyowa Chemical Industry Co., Ltd., etc.). The amount of the silane coupling agent used to treat the surface of the inorganic filler is not particularly limited, but is, for example, 3 mass% or less.
[0032] <Silane coupling agent> The silane coupling agent has a grafting reaction site (group or atom) that can undergo grafting reaction with a grafting reaction site of a chlorine-containing resin or the like in the presence of a radical generated by decomposition of an organic peroxide. Also, it has a hydrolyzable silyl group as a reaction site that can react with a chemically bondable site of an inorganic filler and can undergo silanol condensation. Any silane coupling agent of this type can be used without any particular limitation. Examples of such silane coupling agents include silane coupling agents used in conventional silane crosslinking methods. Examples of the silane coupling agent include silane coupling agents having an unsaturated group, and specifically include vinyl alkoxy silanes such as vinyl trimethoxy silane, vinyl triethoxy silane, vinyl tributoxy silane, vinyl dimethoxy ethoxy silane, vinyl dimethoxy butoxy silane, vinyl diethoxy butoxy silane, allyl trimethoxy silane, allyl triethoxy silane, and vinyl triacetoxy silane, and (meth) acryloxy alkoxy silanes such as methacryloxy propyl trimethoxy silane, methacryloxy propyl triethoxy silane, and methacryloxy propyl methyl dimethoxy silane. Among them, vinyl trimethoxy silane or vinyl triethoxy silane is particularly preferred. The silane coupling agent may be used as it is, or may be used after being diluted with a solvent.
[0033] <Silanol condensation catalyst> The silanol condensation catalyst acts to promote the condensation reaction in the presence of moisture of the hydrolyzable silyl group of the silane coupling agent grafted to the chlorine-containing resin, etc. Based on the action of this silanol condensation catalyst, the chlorine-containing resin, etc. is crosslinked via the silane coupling agent. Such silanol condensation catalysts are not particularly limited, and examples thereof include organotin compounds, metal soaps, platinum compounds, etc. Examples of organotin compounds include dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin dioctiate, dibutyltin diacetate, and other organotin compounds.
[0034] <Other polymers> In the present invention, polymers (including resins, elastomers, and rubbers) other than chlorine-containing resins and ethylene-carbon monoxide copolymers can also be used. Examples include polyolefin resins, fluororesins, fluororubbers, and various elastomers.
[0035] <Additives> In the present invention, various additives generally used in resin compositions may be appropriately blended within the range that does not impair the effects of the present invention. Examples of such additives include crosslinking assistants, antioxidants, lubricants, metal deactivators, flame retardants (assistants), etc. Examples of the antioxidants include, but are not limited to, amine antioxidants, phenol antioxidants, sulfur antioxidants, etc.
[0036] <Method of manufacturing chlorine-containing crosslinked resin molded product> The method for producing a chlorine-containing crosslinked resin molded article of the present invention will now be described in detail. The method for producing a chlorine-containing crosslinked resin molded article of the present invention (sometimes simply referred to as the production method of the present invention) includes the following steps (1), (2), and (3). The chlorine-containing resin and the ethylene-carbon monoxide copolymer used in the production method of the present invention are as described above.
[0037] Step (1): 15 to 100 parts by mass of ethylene-carbon monoxide copolymer is mixed with 100 parts by mass of chlorine-containing resin. 70 parts by mass, 30 to 100 parts by mass of plasticizer, and 0.01 to 0. 5 parts by mass, 0.5 to 50 parts by mass of inorganic filler, and Grafting reaction capable of reacting with chlorine-containing resins in the presence of radicals. 1 to 10 parts by mass of a silane coupling agent having a silanol condensation catalyst and mixed in a melt, and grafted by the radicals generated from the organic peroxide. The reactive site is grafted with a site capable of grafting reaction of a chlorine-containing resin. A process for preparing a chlorine-containing crosslinkable resin composition by Step (2): A step of obtaining a molded product by injection molding the chlorine-containing crosslinkable resin composition. Step (3): A step of contacting the molded product with water to obtain a chlorine-containing crosslinked resin molded product.
[0038] The above step (1) includes the following steps depending on the use mode of the chlorine-containing resin. That is, when the entire chlorine-containing resin is melt-mixed in the following step (a-2), step (1) includes the following steps (a-1), (a-2), and (c). On the other hand, when a part of the chlorine-containing resin is melt-mixed in the following step (a-2), step (1) includes the following steps (a-1), (a-2), (b), and (c). Step (a-1): A step of mixing an inorganic filler and a silane coupling agent to prepare a mixture. Process Step (a-2): Reacting the resulting mixture with all or a part of the chlorine-containing resin and ethylene-carbon monoxide The copolymer and the plasticizer are mixed in the presence of an organic peroxide at a decomposition temperature of the organic peroxide. The grafting reaction sites and the grafting reaction sites are melt-mixed at a temperature of 100° C. or higher. By grafting the reactive sites, the silane masterbatch can be formed. Preparing the batch Step (b): The remainder of the chlorine-containing resin and the silanol condensation catalyst are melt-mixed to form a catalyst masterbatch. Preparing the batch Step (c): Mixing the silane master batch with a silanol condensation catalyst or catalyst master batch. A step of melt mixing to prepare a chlorine-containing crosslinkable resin composition.
[0039] In the above step (b), the remainder of the chlorine-containing resin that is mixed with the silanol condensation catalyst is sometimes referred to as a carrier resin. In addition, both steps (a-1) and (a-2) may be collectively referred to as step (a).
[0040] As described above, the production method of the present invention includes an embodiment in which a chlorine-containing resin is added to step (a-2) and used in step (b). In this case, 100 parts by mass of the chlorine-containing resin in step (1) is the total amount of the chlorine-containing resin mixed in step (a-2) and step (b). Here, the chlorine-containing resin used in step (a-2) and step (b) is not particularly limited, and may be chlorinated polyethylene, polyvinyl chloride, or a mixture of these. Preferably, chlorinated polyethylene that undergoes a grafting reaction is used in step (a-2), and polyvinyl chloride that does not undergo a grafting reaction is used as a carrier resin in step (b). The ethylene-carbon monoxide copolymer may be mixed in either step (a-2) or step (b), but is preferably mixed in step (a-2) in terms of its ease of grafting reaction. When the remainder of the chlorine-containing resin is blended in step (b), the chlorine-containing resin is blended in an amount of preferably 70 to 95 mass%, more preferably 85 to 92 mass%, in step (a-2), and in an amount of preferably 5 to 30 mass%, more preferably 8 to 15 mass%, in step (b).
[0041] In step (1), the mixing amount (blending amount) of the ethylene-carbon monoxide copolymer is 15 to 70 parts by mass relative to 100 parts by mass of the chlorine-containing resin. In the present invention, since the ethylene-carbon monoxide copolymer is used in combination with the chlorinated polyethylene and polyvinyl chloride, high oil resistance can be achieved by making the content of the ethylene-carbon monoxide copolymer 15% by mass or more. On the other hand, a decrease in injection moldability can be effectively suppressed by making it 70% by mass or less. The mixing amount of the ethylene-carbon monoxide copolymer is preferably 20 to 50 parts by mass, more preferably 20 to 35% by mass relative to 100 parts by mass of the chlorine-containing resin, in terms of providing high oil resistance and heat resistance and suppressing a decrease in injection moldability.
[0042] In step (1), the mixing amount of the plasticizer is 30 to 100 parts by mass relative to 100 parts by mass of the chlorine-containing resin. When the plasticizer is melt-mixed in this mixing amount, the injection moldability can be improved without significantly impairing the high oil resistance and heat resistance. The mixing amount of the plasticizer is preferably 50 to 80 parts by mass, more preferably 50 to 65% by mass, relative to 100 parts by mass of the chlorine-containing resin, in order to achieve a good balance between high oil resistance, heat resistance, and injection moldability. When the plasticizer is mixed in step (b), the mixing amount is a part of the above mixing amount, for example, preferably 3 to 20 parts by mass, more preferably 5 to 15 parts by mass.
[0043] In step (1), the amount of the organic peroxide mixed is 0.01 to 0.5 parts by mass, preferably 0.05 to 0.2 parts by mass, and more preferably 0.05 to 0.12 parts by mass, relative to 100 parts by mass of the chlorine-containing resin. By making the amount of the organic peroxide mixed 0.01 to 0.5 parts by mass, the grafting reaction can be carried out in an appropriate range, and condensation between the silane coupling agents can be suppressed, thereby suppressing the occurrence of gel particles or roughness in the molded product, thereby preventing deterioration of the appearance.
[0044] In step (1), the amount of the inorganic filler mixed is 0.5 to 50 parts by mass, preferably 3 to 30 parts by mass, and more preferably 10 to 20 parts by mass, relative to 100 parts by mass of the chlorine-containing resin. By setting the amount of the inorganic filler mixed to 0.5 to 50 parts by mass, high oil resistance, heat resistance, and injection moldability can be achieved in a well-balanced manner.
[0045] In step (1), the amount of the silane coupling agent mixed is 1 to 10 parts by mass, preferably 2 to 8 parts by mass, and more preferably 2 to 6 parts by mass, relative to 100 parts by mass of the chlorine-containing resin. When the amount of the silane coupling agent mixed is 1 to 10 parts by mass, the crosslinking reaction can be moderately advanced, and both high heat resistance and injection moldability can be achieved. In addition, the silane coupling agent is adsorbed on the surface of the inorganic filler, and the silane coupling agent can be prevented from volatilizing during kneading, which is economical. Furthermore, the silane coupling agent that is not adsorbed can be prevented from condensing, causing gel particles or roughness in the molded body, thereby preventing the appearance from deteriorating.
[0046] In step (1), the amount of the silanol condensation catalyst is not particularly limited and is appropriately set. For example, it is preferably 0.03 to 0.5 parts by mass, more preferably 0.03 to 0.2 parts by mass, and even more preferably 0.05 to 0.15 parts by mass, relative to 100 parts by mass of the chlorine-containing resin. When the amount of the silanol condensation catalyst is set to 0.03 to 0.5 parts by mass, the crosslinking reaction can be appropriately advanced, achieving both high heat resistance and injection moldability. In addition, the generation of gel particles during molding can be suppressed.
[0047] In carrying out step (1), steps (a-1) and (a-2) are carried out in sequence. That is, first, an inorganic filler and a silane coupling agent are mixed, and then the mixture obtained, all or a part of the chlorine-containing resin, an ethylene-carbon monoxide copolymer, and a plasticizer are melt-kneaded in the above-mentioned mixed amounts while being heated to a temperature equal to or higher than the decomposition temperature of the organic peroxide, thereby inducing the above-mentioned grafting reaction to prepare a silane master batch (Silane MB). In the present invention, the order of mixing when "melting and mixing the mixture with all or a part of the chlorine-containing resin, the ethylene-carbon monoxide copolymer, and the plasticizer" is not particularly limited, and means that each component may be mixed in any order. That is, the order of mixing in step (a-2) is not particularly limited. For example, the mixture, the chlorine-containing resin, the ethylene-carbon monoxide copolymer, the plasticizer, and the remaining components may be melt-mixed at once, or the mixture, the chlorine-containing resin, and the plasticizer may be mixed in the same manner as the dry processing mixing in step (a-1) described later (preferably dry blending the powders), and then the obtained mixture and the remaining components, such as the ethylene-carbon monoxide copolymer and other components, may be melt-mixed. In addition, the method of mixing the chlorine-containing resin is not particularly limited. For example, a chlorine-containing resin that has been mixed and prepared in advance may be used, or each component may be mixed separately.
[0048] In step (1), first, the inorganic filler and the silane coupling agent are mixed using an appropriate mixing device to prepare a mixture (step (a-1)). The premixed silane coupling agent is present so as to surround the surface of the inorganic filler, and it is considered that a part or all of it is adsorbed or bonded to the inorganic filler. This allows a well-balanced formation of a silane coupling agent that is weakly bonded or adsorbed to the inorganic filler and a silane coupling agent that is strongly bonded or adsorbed to the inorganic filler. Here, for the silane coupling agent, examples of the weak bond with the inorganic filler include interactions due to hydrogen bonds, interactions between ions, partial charges or dipoles, and actions due to adsorption. Examples of the strong bond with the inorganic filler include chemical bonds with sites on the inorganic filler surface that can be chemically bonded. In addition, the above step (a-1) can reduce the volatilization of the silane coupling agent during subsequent melt mixing, and can also prevent the silane coupling agent that is not adsorbed or bonded to the inorganic filler from condensing, making melt kneading difficult.
[0049] The method of premixing the inorganic filler and the silane coupling agent is not particularly limited, but includes mixing methods such as wet processing and dry processing. Specifically, the inorganic filler and the silane coupling agent are mixed by dry or wet processing for several minutes to several hours at a temperature below the decomposition temperature of the organic peroxide, preferably 10 to 60°C, more preferably around room temperature (20 to 25°C), and more preferably, dry processing in which the silane coupling agent is added to the inorganic filler, preferably the dried inorganic filler, with or without heating and mixed is more preferable. In step (a-1), the chlorine-containing resin and the ethylene-carbon monoxide copolymer may be mixed as long as the temperature is maintained below the decomposition temperature.
[0050] In the manufacturing method of the present invention, the mixture of inorganic filler and silane coupling agent obtained in step (a-1), all or part of chlorine-containing resin, and the remaining components that are not mixed in step (a-1) are melt-mixed in the presence of organic peroxide while heating to a temperature equal to or higher than the decomposition temperature of organic peroxide (step (a-2)). By step (a-2), excessive crosslinking reaction between chlorine-containing resin components can be prevented, and a crosslinked molded product with excellent appearance can be obtained. By the melt mixing in step (a-2), the radicals generated from the organic peroxide cause a grafting reaction between the grafting reaction site of the silane coupling agent and the grafting reaction site of the chlorine-containing resin, etc., to undergo a grafting reaction. As a result, a silane crosslinkable chlorine-containing resin, etc., in which the silane coupling agent is covalently bonded to the chlorine-containing resin, etc., is synthesized, and a silane MB containing this silane crosslinkable chlorine-containing resin, etc. is prepared. In step (a-2), the grafting reaction of the silane coupling agent to the chlorine-containing resin, etc. can be at least as follows. That is, the silane coupling agent bonded or adsorbed to the inorganic filler by a weak bond is detached from the inorganic filler and grafted to the chlorine-containing resin, etc. The crosslinked structure formed in this mode does not incorporate the inorganic filler, and is usually a crosslinked structure via a silanol condensate between the silane coupling agents. In addition, the silane coupling agent bonded or adsorbed to the inorganic filler by a strong bond is grafted to the chlorine-containing resin, etc., while maintaining the bond with the inorganic filler. The crosslinked structure formed in this manner incorporates the inorganic filler, and is a crosslinked structure starting from the inorganic filler via the silane coupling agent bonded thereto. In this process, the silane coupling agent may also undergo a grafting reaction with the ethylene-carbon monoxide copolymer while maintaining the bonded or adsorbed state with the inorganic filler.
[0051] In step (a-2), the temperature at which the above components are melted and mixed is equal to or higher than the decomposition temperature of the organic peroxide, preferably equal to or higher than the decomposition temperature of the organic peroxide + (25 to 110)°C, and more preferably equal to or higher than 150 to 230°C. At the above mixing temperature, the above components melt, the organic peroxide decomposes, and the necessary silane grafting reaction proceeds sufficiently in step (a-2). Other conditions can be set as appropriate. For example, the mixing time is set as appropriate within the range of 3 to 40 minutes. The decomposition temperature of the organic peroxide is preferably equal to or higher than the temperature at which the chlorine-containing resin melts. The mixing method is not particularly limited as long as it is a method commonly used for rubber, plastics, etc. As a kneading device, a single screw extruder, a twin screw extruder, a roll, a Banbury mixer, various kneaders, etc. are used. In terms of dispersibility of the chlorine-containing resin, etc., and stability of the crosslinking reaction, a closed type mixer such as a Banbury mixer or various kneaders is preferred.
[0052] The organic peroxide and the ethylene-carbon monoxide copolymer may be present during the melt mixing in the above step (a-2), i.e., when the mixture obtained in step (a-1) is melt mixed with the chlorine-containing resin. These components may be mixed, for example, in step (a-1) or in step (a-2). The organic peroxide is preferably mixed in step (a-1), and the ethylene-carbon monoxide copolymer is preferably mixed in step (a-2). It is sufficient that a part of the plasticizer is present during the melt mixing in the above step (a-2), and the plasticizer may be mixed in either step (a-1) or step (a-2). The plasticizer is preferably mixed in step (a-2), but the remainder may be mixed in step (b) described below.
[0053] In steps (a-1) and (a-2), especially in step (a-2), it is preferable to melt-mix the above-mentioned components without substantially mixing a silanol condensation catalyst. This can suppress the condensation reaction of the silane coupling agent. Here, "substantially not mixed" does not mean to exclude the silanol condensation catalyst that is inevitably present, but means that it may be present to the extent that the above-mentioned problems due to silanol condensation of the silane coupling agent do not occur. For example, in step (a-2), the silanol condensation catalyst may be present in an amount of 0.01 parts by mass or less relative to 100 parts by mass of the chlorine-containing resin.
[0054] In this way, step (a), which consists of steps (a-1) and (a-2), is carried out to graft react the silane coupling agent with the chlorine-containing resin and, if necessary, with the ethylene-carbon monoxide copolymer to prepare Silane MB. Silane MB is a mixture containing the silane crosslinkable chlorine-containing resin, etc., in which the silane coupling agent has been graft reacted with the chlorine-containing resin, etc., to such an extent that it can be molded in step (2) described below.
[0055] In the production method of the present invention, when a part of the chlorine-containing resin is melt-mixed in step (a-2), the remaining part of the chlorine-containing resin is melt-mixed with the silanol condensation catalyst to prepare a catalyst master batch (catalyst MB) in step (b). Therefore, when the whole of the chlorine-containing resin is melt-mixed in step (a-2), step (b) does not need to be performed, and other chlorine-containing resin components may be mixed with the silanol condensation catalyst.
[0056] The mixing ratio of the remainder of the chlorine-containing resin as the carrier resin and the silanol condensation catalyst is not particularly limited, but is preferably set so as to satisfy the above-mentioned blending amount in step (1). The mixing may be performed by any method that can achieve uniform mixing, including mixing (melt mixing) performed under molten chlorine-containing resin. Melt mixing can be performed in the same manner as in the melt mixing in the above step (a-2). For example, the mixing temperature can be appropriately set to a temperature equal to or higher than the melting temperature of the chlorine-containing resin component, and is preferably 120 to 200°C, more preferably 140 to 180°C. Other conditions, such as the mixing time, can be appropriately set.
[0057] In step (b), instead of or in addition to the remainder of the chlorine-containing resin, another resin can be used as a carrier resin in an appropriate amount. That is, in step (b), the remainder of the chlorine-containing resin when a part of the chlorine-containing resin is melt-mixed in step (a-2), or a resin other than the chlorine-containing resin used in step (a-2) may be melt-mixed with the silanol condensation catalyst to prepare a catalyst master batch. In step (b), an inorganic filler or a plasticizer can be mixed. In this case, the blending amounts of the inorganic filler and the plasticizer are not particularly limited and are appropriately set in consideration of the above blending amounts. For example, the plasticizer can be 3 to 20 parts by mass. In the case where a chlorine-containing resin and a plasticizer are used in step (b), it is preferable to first premix the chlorine-containing resin and the plasticizer under the dry processing mixing conditions of the above-mentioned step (a-1), and then melt-mix the obtained premix with the silanol condensation catalyst and, if appropriate, the remaining components. The catalyst MB thus prepared is a (molten) mixture of the silanol condensation catalyst and the carrier resin, optionally with added fillers or plasticizers.
[0058] In the process of the present invention, step (c) is then carried out in which the silane MB and the silanol condensation catalyst or catalyst MB are melt-mixed to prepare a chlorine-containing crosslinkable resin composition. The mixing method may be any method as long as a homogeneous reaction composition can be obtained as described above, and is basically the same as the melt mixing in step (a-2). Mixing is performed at a temperature at which the chlorine-containing resin melts. The melt mixing temperature is appropriately selected according to the melting temperature of the chlorine-containing resin or the carrier resin, and is, for example, preferably 80 to 250°C, more preferably 100 to 240°C, and even more preferably 120 to 200°C. Other conditions, such as the mixing time, can be appropriately set. In step (c), in order to avoid silanol condensation reactions, it is preferable that the mixture of silane MB and silanol condensation catalyst is not kept at high temperature for a long period of time. When carrying out this step (c), the silane master batch and the silanol condensation catalyst or catalyst MB may be dry-blended and then melt-mixed. The conditions for dry blending are not particularly limited, but may be, for example, the dry mixing conditions of the above step (a-1).
[0059] In this manner, steps (a) to (c) (step (1)) are carried out to prepare a chlorine-containing crosslinkable resin composition. This chlorine-containing crosslinkable resin composition contains a chlorine-containing resin such as the silane-crosslinkable chlorine-containing resin, an ethylene-carbon monoxide copolymer, a plasticizer, an inorganic filler, a silanol condensation catalyst, and the like. This chlorine-containing crosslinkable resin composition contains silane crosslinkable chlorine-containing resins, etc., which have different crosslinking methods. In this silane crosslinkable chlorine-containing resin, etc., the silane coupling agent's reactive site capable of silanol condensation may be bonded or adsorbed to an inorganic filler, but as described below, it is not silanol condensed. Therefore, the silane crosslinkable chlorine-containing resin, etc., includes at least a crosslinkable chlorine-containing resin, etc., in which a silane coupling agent bonded or adsorbed to an inorganic filler is grafted to a chlorine-containing resin, etc., and a crosslinkable chlorine-containing resin, etc., in which a silane coupling agent not bonded or adsorbed to an inorganic filler is grafted to a chlorine-containing resin, etc. As described above, the silane crosslinkable chlorine-containing resin is an uncrosslinked body in which the silane coupling agent is not condensed with silanol. In practice, when melt-mixed in step (c), partial crosslinking is inevitable, but the obtained chlorine-containing crosslinkable resin composition has at least the injection moldability in the injection molding in step (2).
[0060] In step (1), steps (a) to (c) can be carried out simultaneously or consecutively.
[0061] In step (1), the additives may be mixed in any step, but are preferably mixed into the catalyst MB.
[0062] In the manufacturing method of the present invention, the step (2) of injection molding the obtained chlorine-containing crosslinkable resin composition to obtain a molded body is then carried out. In this step (2), it is sufficient to be able to injection mold the chlorine-containing crosslinkable resin composition, and the injection molding conditions are appropriately selected according to the chlorine-containing crosslinkable resin composition of the present invention. The injection molding temperature is set to a temperature equal to or higher than the temperature at which the chlorine-containing crosslinkable resin composition melts, and cannot be determined univocally. For example, it is preferable to set the nozzle temperature to about 190 to 230°C, the rear part of the cylinder (feeder side) to about 170 to 220°C, the middle part of the cylinder to about 170 to 220°C, the front part of the cylinder (nozzle side) to about 180 to 220°C, and the mold temperature to about 25 to 40°C. Other injection molding conditions are not particularly limited and are appropriately set according to the physical properties of the chlorine-containing crosslinkable resin composition, and examples thereof include the injection molding conditions adopted in the examples. The injection molding can be carried out using a general-purpose injection molding machine for plastics, and the mold is appropriately selected depending on the shape, dimensions, etc. of the molded article.
[0063] Moreover, step (2) can be carried out simultaneously with or consecutively to step (c). That is, one embodiment of the melt mixing in step (c) is to melt mix the molding raw materials during or immediately before injection molding. For example, pellets such as dry blends may be mixed together at room temperature or high temperature and introduced into an injection molding machine (melt mixing), or may be melt mixed after mixing, pelletized again, and introduced into an injection molding machine. More specifically, a series of steps can be adopted in which a molding material consisting of silane MB and silanol condensation catalyst or catalyst MB is melt mixed (melt kneaded) in an injection molding machine, and then injection molded into a mold of a desired shape. In this way, an (injection) molded article of the chlorine-containing crosslinkable resin composition is obtained. This injection molded article is in an uncrosslinked or partially crosslinked state that maintains the injection moldability that allows injection molding in step (2) although partial crosslinking is inevitable, similar to the chlorine-containing crosslinkable resin composition. Therefore, this injection molded article becomes a crosslinked or final crosslinked silane crosslinked molded article by carrying out step (3).
[0064] In the manufacturing method of the present invention, the molded product obtained in step (2) is then contacted with water in step (3). This causes the silanol condensable reactive sites (hydrolyzable silyl groups) of the silane coupling agent to be hydrolyzed to silanol groups, which then condense with other silanol groups (hydroxyl groups) to cause a crosslinking reaction. In this way, a chlorine-containing crosslinked resin molded product in which the silane coupling agent is crosslinked by silanol condensation can be obtained. The treatment in step (3) itself can be carried out by a normal method. The condensation reaction between silane coupling agents proceeds simply by leaving the silane coupling agents at room temperature, for example, at a temperature of about 20 to 25°C. Therefore, in step (3), it is not necessary to actively bring the molded body into contact with water. In order to promote this crosslinking reaction, the molded body can also be actively brought into contact with water. For example, a method of actively bringing the molded body into contact with water, such as immersion in warm water, immersion in a moist heat bath, or exposure to high-temperature steam, can be used. In addition, pressure may be applied at this time to allow the moisture to penetrate into the interior.
[0065] In this way, a chlorine-containing crosslinked resin molding is produced from the chlorine-containing crosslinkable resin composition. The chlorine-containing crosslinked resin molding contains a chlorine-containing crosslinked resin in which a chlorine-containing resin or the like is condensed through a siloxane bond. The chlorine-containing crosslinked resin molding contains an inorganic filler, and the inorganic filler may be bonded to a silane coupling agent of the chlorine-containing crosslinked resin. Therefore, the chlorine-containing crosslinked resin contains at least a chlorine-containing crosslinked resin in which a plurality of chlorine-containing resins or the like are bonded or adsorbed to the inorganic filler by the silane coupling agent, and bonded (crosslinked) through the inorganic filler and the silane coupling agent, and a chlorine-containing crosslinked resin in which the reactive sites of the silane coupling agent of the chlorine-containing resin or the like are hydrolyzed and undergo a silanol condensation reaction with each other, and crosslinked through the silane coupling agent.
[0066] As described above, the manufacturing method of the present invention is a silane crosslinking method having a series of steps (1) to (3), in which the above-mentioned chlorine-containing resin, ethylene-carbon monoxide copolymer, and plasticizer are used in combination with each component essential to the silane crosslinking method. Therefore, in a series of steps, particularly step (1), the above-mentioned chlorine-containing resin, ethylene-carbon monoxide copolymer, plasticizer, and inorganic filler exhibit the above-mentioned functions while a predetermined grafting reaction proceeds, and a chlorine-containing crosslinkable resin composition with excellent injection moldability is prepared. Then, by subjecting this chlorine-containing crosslinkable resin composition to a silanol condensation reaction after injection molding to form the above-mentioned silane crosslinked structure, the characteristics or functions of each component are effectively expressed, and a chlorine-containing crosslinked resin molded product exhibiting high oil resistance and heat resistance can be produced. In this way, the production method of the present invention can produce a chlorine-containing crosslinked resin molded article that has high oil resistance and heat resistance and is preferably free of injection molding defects (excellent appearance and shape characteristics, low cost) by a simple silane crosslinking method (which allows crosslinking even without heating), that is, by not requiring the conventional crosslinking step, and with energy saving and high productivity. EXAMPLES
[0067] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these. In Tables 1-1 and 1-2 (collectively referred to as Table 1), the numerical values for the blending amount (content) of each example are in parts by mass unless otherwise specified. Also, for each component, a blank space means that the blending amount of the corresponding component is 0 parts by mass. The "Crosslinkable resin composition" column in Table 1 shows the total content of silane MB and catalyst MB, which are essential components of the present invention.
[0068] Details of each compound used in the examples and comparative examples are given below. <Chlorine-containing resin> Polyvinyl chloride: ZEST 1400Z (product name), average degree of polymerization 1450, manufactured by Shin-Daiichi Vinyl Corporation Chlorinated polyethylene: CPE 140B (product name), chlorine content 40%, manufactured by Weifang Yaxing Chemical Co., Ltd. <Ethylene-carbon monoxide copolymer> Ethylene-butyl acrylate-carbon monoxide copolymer: Elvaloy HP662 (trade name), manufactured by DuPont Ethylene-vinyl acetate-carbon monoxide copolymer: Elbaloy 742 (trade name), manufactured by DuPont <Ethylene-vinyl acetate copolymer> Ethylene-vinyl acetate copolymer: Evaflex EV150 (product name), ethylene content 67% by mass, vinyl acetate content 33% by mass, manufactured by Dow Mitsui Polychemicals <Plasticizer> Diisononyl phthalate: DINP, manufactured by J-Plus <Inorganic filler> Fumed silica: KONASIL K-200D (product name), manufactured by OCI Calcium carbonate: Softon 1200 (product name), manufactured by Bihoku Funka Kogyo Co., Ltd. Hydrotalcite: DHT-4A-2 (product name), manufactured by Bihoku Funka Kogyo Co., Ltd. <Silane coupling agent> KBM-1003: Product name, vinyltrimethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd. <Organic peroxide> Perhexa 25B: Trade name, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, manufactured by NOF Corporation <Antioxidants> Irganox 1076: Trade name, octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, manufactured by BASF <Silanol condensation catalyst> Adeka STAB OT-1: Product name, dioctyltin dilaurate, manufactured by ADEKA Corporation
[0069] (Examples 1 to 11 and Comparative Examples 1 to 13) In Examples 1 to 11 and Comparative Examples 1 to 13, a part of polyvinyl chloride among chlorine-containing resins (specifically, the mass proportion shown in the "Step (b) Catalyst MB" column in Table 1) was used as a carrier resin for catalyst MB. First, the inorganic filler, the silane coupling agent, and the organic peroxide were charged into a rotary blade mixer (Mazera PM: product name, manufactured by Mazera Co., Ltd.) in the mass ratio shown in the "Step (a) Silane MB" column of Table 1, and stirred (premixed) for 1 minute at a mixing temperature of 25°C and a rotation speed of 10 rpm to obtain a mixture (step (a-1)). Next, the chlorine-containing resin and the plasticizer were added to the rotary blade mixer in the mass ratio shown in the "Step (a) Silane MB" column of Table 1, and stirred for 5 minutes at a mixing temperature of 25°C and a rotation speed of 10 rpm. Then, the obtained powder mixture, ethylene-carbon monoxide copolymer, and antioxidant were added to a kneader (volume 75 L) preheated to 150°C in the mass ratio shown in the "Step (a) Silane MB" column of Table 1, and mixed for 5 minutes at a rotation speed of 40 rpm, and then further finished kneaded for 3 minutes at a rotation speed of 30 rpm. After confirming that the temperature of the mixture reached 180 to 200°C, which is higher than the decomposition temperature of the organic peroxide, the molten mixture was pelletized using a feeder-ruder and a pelletizer to prepare Silane MB (step (a-2)). However, in Comparative Example 5, Silane MB was prepared in the same manner as in Example 1, except that the components shown in the "Step (a) Silane MB" column of Table 1 were charged into a kneader (volume 75 L) that had been preheated to 150°C in the mass ratio shown in the same column and mixed all at once.
[0070] On the other hand, the chlorine-containing resin and the plasticizer were charged into a rotary blade mixer (Mazera PM) in the mass ratio shown in the "Step (b) Catalyst MB" column of Table 1, and stirred for 5 minutes at a mixing temperature of 25°C and a rotation speed of 10 rpm. Next, the obtained mixture, the antioxidant, and the silanol condensation catalyst were sequentially charged into a kneader (volume 75 L) preheated to 130°C in the mass ratio shown in the "Step (b) Catalyst MB" column of Table 1, and mixed for 5 minutes at a rotation speed of 30 rpm, and then further kneaded for 3 minutes at a rotation speed of 25 rpm. After the temperature of the mixture reached about 160°C and it was confirmed that the chlorine-containing resin was sufficiently melted, the molten mixture was pelletized using a feeder-ruder and a pelletizer to prepare catalyst MB (step (b)).
[0071] Next, Silane MB and Catalyst MB were put into a sealed ribbon blender and dry blended for 5 minutes at a mixing temperature of 25°C to obtain a dry blend. At this time, the mixing ratio of Silane MB and Catalyst MB was the mass ratio shown in the "Step (a) Silane MB" and "Step (b) Catalyst MB" columns of Table 1, and the mass ratio shown in the "Crosslinkable resin composition" column of Table 1. For example, in Example 1, the mixing amount of the chlorine-containing resin in Silane MB was 90 parts by mass, and the mixing amount of the chlorine-containing resin in Catalyst MB was 10 parts by mass.
[0072] Next, using a 50t injection molding machine (ROBOSHOT α-50iA: product name, manufactured by Fanuc Corporation) with a screw diameter of 26 mm, the injection temperature conditions were set as follows: nozzle temperature 200°C, followed by 200°C at the front, 190°C at the middle, 180°C at the rear on the feeder side, and a mold temperature of 30°C. A mold with a JIS-specified "A4" size (210mm x 297mm) and a cavity 2mm thick was prepared. The prepared dry blend was put into this injection molding machine and, while melt-mixing (step (c)) under the following injection molding conditions, injected into a mold to obtain a sheet-like uncrosslinked resin molded product (step (2)). A chlorine-containing crosslinkable resin composition is prepared by the melt-mixing in the above step (c). (Injection molding conditions) Number of nozzles: 1 Nozzle diameter: 3mm Filling pressure: 7MPa Injection speed: 100mm / sec Holding pressure: 3MPa Packing time (time from start of injection to end of packing): 10 seconds Cooling time: 30 seconds
[0073] The obtained sheet-like uncrosslinked resin molded article was left to stand in a room temperature environment (23° C., 50% RH) for 48 hours to contact with water, thereby allowing a silanol condensation reaction (silane crosslinking) to proceed (step (3)). In this manner, a sheet sample of the chlorine-containing crosslinked resin molded article having a thickness of 2 mm and an "A4" size was produced.
[0074] The obtained sheet samples were subjected to the following test methods to evaluate the properties. <Test 1: Tensile test> From each sheet sample, a dumbbell-shaped No. 3 test piece was prepared as specified in JIS K 6251. Using this test piece, the tensile strength (MPa) and tensile elongation (%) were measured under the conditions of a gauge length of 20 mm and a tensile speed of 500 mm / min according to JIS K 6251. The obtained tensile strength and tensile elongation were applied to the following evaluation criteria to evaluate the tensile properties of the test pieces. This test is a reference test to measure tensile properties that will serve as the basis for the oil resistance tensile test described later. (Evaluation criteria for tensile strength) A: 7.0MPa or more (extremely excellent) B: 5.5MPa or more, less than 7.0MPa (excellent) C: 4.0MPa or more, less than 5.5MPa (good) D: Less than 4.0MPa (failed) (Evaluation criteria for tensile elongation) A: 450% or more (extremely excellent) B: 375% or more, less than 450% (excellent) C: 300% or more, less than 375% (good) D: Less than 300% (failed)
[0075] <Test 2: Oil resistance tensile test> From each sheet sample, a dumbbell-shaped test sample of No. 3 as specified in JIS K 6251 was prepared. This test piece was immersed in No. 2 diesel oil as specified in JIS K 2204 at 120°C (diesel temperature) for 18 hours. The test piece was then removed and left to stand at 23°C for 24 hours, after which the oil was thoroughly wiped off, and the tensile strength (MPa) and tensile elongation (%) of the test piece after immersion were measured according to JIS K 6251 under conditions of a gauge length of 20 mm and a tensile speed of 500 mm / min. The tensile strength of the test piece after immersion was divided by the tensile strength before immersion (the tensile strength obtained in the above Test 1: Tensile Test) to calculate the tensile strength retention (%) of the test piece after immersion. Similarly, the tensile elongation retention (%) of the test piece after immersion was calculated. The calculated tensile strength retention and tensile elongation retention were applied to the following evaluation criteria to evaluate the oil resistance of the test piece. The following evaluation criteria "A" indicates a high level of oil resistance that exceeds conventional oil resistance. (Evaluation criteria for tensile strength retention and tensile elongation retention) A: 80% or more (extremely excellent) B: 70% or more, less than 80% (excellent) C: 60% or more, less than 70% (good) D: Less than 60% (failed)
[0076] <Test 3: Injection moldability test> The appearance and shape of each sheet sample were observed, and the injection moldability of the chlorine-containing crosslinkable resin composition and the chlorine-containing crosslinked resin molded article was judged according to the following evaluation criteria. The proportion of the chlorine-containing crosslinkable resin composition that permeated into the cavity was calculated by the following formula. Calculation formula: (mass of the prepared sheet sample [g]) / (mass when the chlorine-containing crosslinkable resin composition is spread throughout the entire cavity [g]) Here, the mass when the chlorine-containing crosslinkable resin composition spreads throughout the entire cavity was calculated by measuring the specific gravity of the prepared sheet sample at 20°C in accordance with JIS K 0061:2001 (Method for measuring density and specific gravity of chemical products) and multiplying the measured specific gravity by the volume of the cavity. This injection moldability test is conducted under harsh conditions using a mold that makes it difficult to inject and fill the molding material into the entire cavity. If the chlorine-containing crosslinkable resin composition fills more than 90% of an A4-sized cavity with a thickness of 2 mm, this is sufficient for injection molding of the connecting materials, molding materials, etc. that will actually be manufactured. Therefore, a score of B or higher is considered to have passed this test. (Evaluation Criteria) A: The chlorine-containing crosslinkable resin composition is distributed throughout the entire cavity of the mold (excellent shape characteristics), and the appearance of the sheet sample is good (no appearance defects such as gel particles or roughness) (excellent injection moldability). B: The chlorine-containing crosslinkable resin composition has permeated 90% or more and less than 100% of the cavity of the mold (excellent shape characteristics), and the appearance of the sheet sample is good (no appearance defects) (good injection moldability) D: The chlorine-containing crosslinkable resin composition filled less than 90% of the cavity of the mold (poor shape characteristics), and gelling or roughness was observed on the surface of the sheet sample (poor appearance) (poor injection moldability: Failed)
[0077] <Test 4: Heat deformation test> A test sample of about 35 mm×35 mm was prepared from each sheet sample. Using this test piece, a heat deformation test was performed based on JIS K 6723 under the conditions of a measurement temperature of 120° C. and a load of 1000 gf. The measured values were applied to the following evaluation criteria to evaluate the heat deformation characteristics (heat resistance). A: 10% or less (excellent) B: More than 10% and less than 20% (excellent) C: Over 20% and under 40% (good) D: Over 40% (fail)
[0078] [Table 1-1]
[0079] [Table 1-2]
[0080] Even if a chlorine-containing crosslinked resin molded body is produced by silane crosslinking (by the manufacturing method of the present invention) after injection molding of the silane crosslinking resin composition shown in Comparative Examples 1 to 13, which does not satisfy the component contents specified in the present invention, high oil resistance and heat resistance cannot be achieved at the same time. In particular, in Comparative Example 5, since the step (a-1) of premixing the inorganic filler, the silane coupling agent, and the organic peroxide was not carried out, the silane coupling agent and the organic peroxide were adsorbed not only to the inorganic filler capable of forming chemical bonds but also to polyvinyl chloride which cannot form a silane crosslinked structure, and a sufficient silane crosslinked structure could not be formed, so that the deformation amount in the heat deformation test was large and sufficient heat resistance was not shown. In contrast, when the silane crosslinking resin composition satisfying the component contents specified in the present invention as shown in Examples 1 to 11 is injection molded and then silane crosslinked (when applied to the manufacturing method of the present invention), a chlorine-containing crosslinked resin molded article that is free of injection molding defects and has both high oil resistance and heat resistance can be produced by a simple method.
Claims
1. A method for producing a chlorine-containing crosslinked resin molded product, comprising the following steps (1), (2) and (3): Step (1): 1 part of ethylene-carbon monoxide copolymer is added to 100 parts by mass of a chlorine-containing resin. 5 to 70 parts by weight, 30 to 100 parts by weight of a plasticizer, and 0.0 parts by weight of an organic peroxide. 1 to 0.5 parts by mass, an inorganic filler of 0.5 to 50 parts by mass, and the organic peroxide. Grafting with the chlorine-containing resin in the presence of radicals generated from an oxide Silane coupling agents 1 to 10 having reactive grafting reaction sites and a silanol condensation catalyst are melt-mixed to obtain a silanol condensation catalyst from the organic peroxide. The radicals generated from the grafting reaction site and the chlorine-containing resin are By subjecting the grafting reaction to a graftable site of the fat, A step of preparing a chlorine-containing crosslinkable resin composition Step (2): A step of obtaining a molded product by injection molding the chlorine-containing crosslinkable resin composition. Step (3): A step of contacting the molded product with water to obtain a chlorine-containing crosslinked resin molded product. the chlorine-containing resin comprises 20 to 50 parts by mass of chlorinated polyethylene and 50 to 80 parts by mass of polyvinyl chloride; the ethylene-carbon monoxide copolymer comprises at least one of an ethylene-vinyl acetate-carbon monoxide copolymer and an ethylene-(meth)acrylic acid ester-carbon monoxide copolymer; In carrying out the step (1), A method for producing a chlorine-containing crosslinked resin molded product, wherein, in the case where the whole of the chlorine-containing resin is melt-mixed in the following step (a-2), the step (1) comprises the following steps (a-1), (a-2), and (c), and, in the case where a part of the chlorine-containing resin is melt-mixed in the following step (a-2), the step (1) comprises the following steps (a-1), (a-2), (b), and (c). Step (a-1): Mixing the inorganic filler and the silane coupling agent to form a mixture A step of preparing Step (a-2): Reacting the mixture, all or a part of the chlorine-containing resin, and ethylene monoxide The carbon copolymer and the plasticizer are mixed in the presence of the organic peroxide. The mixture is melted and mixed at a temperature equal to or higher than the decomposition temperature of the peroxide, and the graph The grafting reaction site and the grafting reaction site are subjected to a grafting reaction. preparing a silane master batch by Step (b): Melt-mixing the remainder of the chlorine-containing resin and the silanol condensation catalyst, A process for preparing a catalyst master batch Step (c): The silane master batch and the silanol condensation catalyst or the catalyst master batch are mixed. The chlorine-containing crosslinkable resin composition is prepared by melt-mixing the star batch. The process
2. The method of claim 1, wherein the ethylene-carbon monoxide copolymer is an ethylene-(meth)acrylic acid ester-carbon monoxide copolymer.
3. The method according to claim 1, wherein the ethylene-carbon monoxide copolymer is melt-mixed in an amount of 20 to 50 parts by mass per 100 parts by mass of the chlorine-containing resin.
4. A method for producing a polyester resin according to any one of claims 1 to 3, wherein the chlorine-containing resin comprises 20 to 35 parts by mass of chlorinated polyethylene and 65 to 80 parts by mass of polyvinyl chloride.
5. A manufacturing method described in any one of claims 1 to 4, wherein the content of the plasticizer is 50 to 80 parts by mass per 100 parts by mass of the chlorine-containing resin.
6. A chlorine-containing crosslinked resin molded body obtained by the manufacturing method described in any one of claims 1 to 5.
Citation Information
Patent Citations
Vinyl chloride resin composition
JP1986113637A
Thermoplastic resin composition
JP1996319389A
Vinyl chloride-based resin composition for injection-molded shoe
JP2004143235A
Vinyl chloride resin composition, and wire and cable using the same
JP2013231134A
Molded body of chlorine-containing heat-resistant crosslinked resin, method for producing said body, silane masterbatch, masterbatch mixture, and heat-resistant product
WO2018180690A1